(untitled) (Journal of the College of Basic Education, 2023)
The aim of the current research is to know (building standards for the performance-based evaluation of Arabic language teachers and its teachers for the preparatory stage), and to achieve the research goal, the researcher adopted the descriptive approach, and the research community consisted of Arabic language teachers and its teachers for the preparatory stage in the six general directorates of education in the province of Baghdad, for the year The academic year 2021-2022, whose number is (2007) teachers and a school, and the researcher randomly chose the research sample, as it reached (90) teachers and schools distributed over the six directorates, with (15) teachers and a school from each directorate. As for the research tool, it was the questionnaire for performance-based evaluation criteria For the preparatory stage, its validity was confirmed by presenting it to a group of arbitrators. The questionnaire included (58) criteria, distributed over four areas: planning (15 criteria), teaching aids, educational techniques and educational activities (12 criteria), implementation and interaction within the classroom environment between Teacher and student (17) criteria, evaluation, processes and outputs (14) criteria, and after collecting data and analyzing the results statistically using the weighted mean and percentage weight, the researcher reached several results, including: The field evaluation, processes and outcomes (ranked first with a weighted average of (2.17), and a weight percentile of (72.07), and the field (educational means and techniques and educational activities) got the last rank with a weighted mean of (1.99), and a weight percentile of (66.25), and in light of the results, the researcher reached To several conclusions, including: The criteria achieved in evaluating the performance of Arabic language teachers and schools in the light of the performance-based evaluation criteria for the preparatory stage accounted for (55.17%) of the performance-based evaluation criteria. Performance-based evaluation criteria for the preparatory stage accounted for (44.83%) of the performance-based evaluation criteria. The researcher also made several recommendations and proposals.Keywords: Building criteria for performance-based evaluation.